2016
DOI: 10.1089/dia.2015.0428
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of Robot Assistant in Management of Type 1 Diabetes in Children

Abstract: Use of robots as a new device to support diabetes self-management in children was well accepted by patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 2 publications
0
24
0
1
Order By: Relevance
“…The developed testbed prototype is still open for further improvements and applications in various fields including self-management of chronic diseases and delivery of healthcare services over a distance using e/m-health platforms (Al-Taee et al, 2015, 2016a, 2016b.…”
Section: Resultsmentioning
confidence: 99%
“…The developed testbed prototype is still open for further improvements and applications in various fields including self-management of chronic diseases and delivery of healthcare services over a distance using e/m-health platforms (Al-Taee et al, 2015, 2016a, 2016b.…”
Section: Resultsmentioning
confidence: 99%
“…Only one of these studies focused on behavioral acceptance as an outcome variable, whereas the other all focused on intentional acceptance. Important to note here is that of the full sample, only six articles explicitly mentioned the concept "acceptance" (Al-Taee et al, 2016;Kanda et al, 2012;Looije et al, 2017;Sabelli & Kanda, 2016;Saint-Aimé, Grandgeorge et al, 2011;Shiomi et al, 2016), of which only four (partly) operationalized it as either intentional (Kanda et al, 2012;Looije et al, 2017;Saint-Aimé, Grandgeorge et al, 2011) or behavioral acceptance (Shiomi et al, 2016). The other 28 articles used measures that were (partly) similar in their operationalization to intentional or behavioral acceptance, but were not explicitly conceptualized as such.…”
Section: Methodological Characteristicsmentioning
confidence: 99%
“…As for a child's sex, three studies found no effect on intentional acceptance of a social robot (Al-Taee et al, 2016;Gomes, Sardinha, Segura, Cramer, & Paiva, 2014;Leite & Lehman, 2016), whereas one study did find an effect on behavioral acceptance (Simmons & Knight, 2017): Girls showed a higher behavioral acceptance of the robot than did boys. Finally, one study (Kȩdzierski, Muszyński, Zoll, Oleksy, & Frontkiewicz, 2013) found positive correlations between various personality traits (i.e., openness to experience and agreeableness) and intentional acceptance, as well as between general interest in robots and intentional acceptance.…”
Section: The Effect Of User Characteristics On Acceptancementioning
confidence: 99%
“…In the case of children, there are studies of assistant robots for children with diabetes [5,25] which have been used in their private or domestic environment (86.7%). In the work [5] one key result was highlighted: "the development of a fully functional prototype and its end-to-end functionality.…”
Section: Robotic Assistantsmentioning
confidence: 99%